Analysis of Supply Chain, Shipping Costs and Consumer Confidence in Purchases on The Shopee E-Commerce Platform in The City of Medan - Cleo Safalingga P; Rahmat Alamsyah Harahap; Nawang Sari KN Ningtias; Novelyn Siregar; Andy Hakim (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
SPX Shopee Express has been operating in Medan since 2018. In the development of the SPX Shopee expedition business, there have been problems with the supply chain, such as overloaded packages, late deliveries, and product damage. There have also been problems with expedition costs, such as inconsistent estimates of product weight and dimensions and the imposition of insurance costs. There have been problems with consumer trust, such as concerns about package delivery fraud and distrust of personal data security. Quantitative descriptive research is the research method, and explanatory research is the nature of the research. Interviews, questionnaires, and documentation studies are the data collection methods. Multiple linear regression with classical assumption testing, namely normality, multicollinearity, and heteroscedasticity, is the analysis method. The population of this study was 300 customers, 171 of whom were selected through simple random sampling, and the validity and reliability were tested on 30 of them. The conclusion of the simultaneous analysis of the supply chain, shipping costs, and consumer confidence (F-test) has a positive effect on the success rate of Fcount 108.488 > Ftable 2.66 with sig. 0.000 < 0.05. Partially (t-test), the supply chain t-count is 1.254 < t-table 1.65392 and sig. 0.212 > 0.05, shipping costs tcount 0.662 < ttable 1.65392 and sig. 0.509 > 0.05, consumer confidence tcount 9.381 > ttable 1.65392 and sig. 0.000 < 0.05. The adjusted R-square coefficient test result of 0.655 means that 65.5% of the supply chain, shipping costs, and consumer confidence affect the success rate at a level of 65.5%, while the remaining 34.5% are other factors that can be explained by other variables.